Migration histories of the medieval Afroeurasian transition zone : aspects of mobility between Africa, Asia and Europe, 300-1500 C.E. - Preiser-Kapeller, Johannes; Reinfandt, Lucian; Stouraitis, Yannis (2020)
"The transition zone between Africa, Asia and Europe was the most important intersection of human mobility in the medieval period. The present volume for the first time systematically covers migration histories of the regions between the Mediterranean and Central Asia and between Eastern Europe and the Indian Ocean in the centuries from Late Antiquity up to the early modern era. Within this framework, specialists from Byzantine, Islamic, Medieval and African history provide detailed analyses of specific regions and groups of migrants, both elites and non-elites as well as voluntary and involuntary. Thereby, also current debates of migration studies are enriched with a new dimension of deep historical time. Contributors are: Alexander Beihammer, Lutz Berger, Florin Curta, Charalampos Gasparis, George Hatke, Dirk Hoerder, Johannes Koder, Johannes Preiser-Kapeller, Lucian Reinfandt, Youval Rotman, Yannis Stouraitis, Panayiotis Theodoropoulos, and Myriam Wissa".